Influence of crystal structure on dielectric properties of Barium Strontium Titanate during high energy ball milling. (2017) - Chowdhury, S.; Mathan Kr., T.; Sen, S.; Mukhopadhyay, A.K.; Ghosh, J.
Abstract: The present study, considering Barium strontium titanate due to its important applications in the electronic device as the piezoelectric material due to excellent performance as sensing and actuation. Barium strontium titanatenanocrystalline ceramic have been synthesized from mechanical alloying of commercially available BaCO3, SrCO3 and TiO2 by high energy ball milling. This method has produced nano-sized particles as well as highly reactive surface, can cause structural relaxation of surface atom and produce inhomogeneous strain by producing defect in crystalline solids and that defect can influence powder properties. The milled powders are characterized at different stages of milling by XRD, particle size analyzer, FESEM and DC electrometer. XRD analysis reveals that barium carbonate slowly transformed into barium strontium carbonate and finally into Barium strontium titanate at 1200°C. This structural transformation gradually reduces the dielectric behavior of the Barium strontiumtitanateatnanoscale.ItwasobservedthatCapacitancedrasticallyreducedfrom20.47pFto3.06pF.